2015
DOI: 10.1002/bjs.9736
|View full text |Cite
|
Sign up to set email alerts
|

Transparent Reporting of a multivariable prediction model for Individual Prognosis Or Diagnosis (TRIPOD): the TRIPOD Statement

Abstract: Background: Prediction models are developed to aid healthcare providers in estimating the probability or risk that a specific disease or condition is present (diagnostic models) or that a specific event will occur in the future (prognostic models), to inform their decision-making. However, the overwhelming evidence shows that the quality of reporting of prediction model studies is poor. Only with full and clear reporting of information on all aspects of a prediction model can risk of bias and potential usefuln… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
692
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 847 publications
(740 citation statements)
references
References 70 publications
10
692
0
2
Order By: Relevance
“…Study results are reported in line with the Transparent Reporting of a multivariable prediction model for Individual Prognosis Or Diagnosis (TRIPOD) statement10. In the UK, the South‐East Scotland Research Ethics Service (reference NR/1506AB4) confirmed that ethical review was not required, as this observational study collected only routine, non‐patient‐identifiable data.…”
Section: Methodssupporting
confidence: 63%
“…Study results are reported in line with the Transparent Reporting of a multivariable prediction model for Individual Prognosis Or Diagnosis (TRIPOD) statement10. In the UK, the South‐East Scotland Research Ethics Service (reference NR/1506AB4) confirmed that ethical review was not required, as this observational study collected only routine, non‐patient‐identifiable data.…”
Section: Methodssupporting
confidence: 63%
“…These results indicate that risk models based on local data accurately predict mortality rate; however, risk models based on data from other countries are unable to accurately predict mortality rate. When evaluating the performance of a prediction model in adherence to the transparent reporting of a multivariable prediction model for individual prognosis or diagnosis guideline, 26 investigators should pay attention to the discrepancy, involving the use of participant data collected by another country for external validation.…”
Section: Discussionmentioning
confidence: 99%
“…Statistical analyses were conducted using R software and SPSS ® version 19.0 (IBM, Armonk, New York, USA). This study was conducted and reported in line with the TRIPOD guidelines16.…”
Section: Methodsmentioning
confidence: 99%